1995
DOI: 10.1007/bf03349816
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic aldosteronoma associated to another adrenocortical adenoma in the adrenal gland of the same side

Abstract: The occurrence of tumors originating from aberrant adrenocortical tissue in ectopic site is very rare. Up to now only two cases of ectopic aldosterone-producing adenoma have been described. We have observed another case of ectopic aldosteronoma, located in the retrocaval region, laterally to the body of the 12th thoracic vertebra. This ectopic tumor was associated to another adrenocortical adenoma, in the adrenal gland of the same side. The diagnostic implications of this observation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Adrenal cortical adenomas have been described in the retrocaval region, spinal canal and suprarenal. [8][9][10] To our knowledge this is the first case of an ectopic virilising tumour that was …”
Section: Discussionmentioning
confidence: 84%
“…Adrenal cortical adenomas have been described in the retrocaval region, spinal canal and suprarenal. [8][9][10] To our knowledge this is the first case of an ectopic virilising tumour that was …”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, tumors arising from adrenal rests are on record, often benign and non-functioning. In a few cases, ectopic tissue may be directly responsible for Conn's syndrome [59] or ACTH-independent Cushing 's syndrome, due to adenomas [27,28,39,60,61] and exceptionally to carcinomas [32,62,63]. Indeed, adenoma is not easily differentiated from normal ectopic tissue, except for an aberrant hormonal production or a large size.…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of hormonally active ectopic adrenal tumor have been described. For instance, Mazza et al found an ectopic aldosteronoma that was located in the retrocava location that were successfully treated by a conventional open approach 5 …”
Section: Discussionmentioning
confidence: 99%